2018
DOI: 10.11114/jets.v6i5.2996
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Self-Efficacy on Physical Activity: A Cross-Cultural Comparision

Abstract: The purpose of this cross-cultural study exposes stages of change for exercise behavior (SCEB) in relation to perceived social self-efficacy (PSSE) between Turkey and England sport sciences students. The study group of the research consists of 168 (66 women and 102 men) students from Turkey and 217 (112 women and 105 men) students from England who completed a questionnaire package that included SCEB scale and The PSSE Scale. Descriptive statistics, t test, ANOVA, Chi-Square test were used as a statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Accordingly, a study conducted by Iso-Ahola [55] reported that voluntary participation in leisure activities improves overall satisfaction with life by increasing self-efficacy. It is noteworthy that the findings that physical activity protects positive mental health are supported not only in Eastern cultures [56,57] but also in Western cultures [58]. Considering that the present study found similar results regarding the participation of immigrants in leisure activities, physical activities should be encouraged not only for physical health but also for psychological aspects.…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, a study conducted by Iso-Ahola [55] reported that voluntary participation in leisure activities improves overall satisfaction with life by increasing self-efficacy. It is noteworthy that the findings that physical activity protects positive mental health are supported not only in Eastern cultures [56,57] but also in Western cultures [58]. Considering that the present study found similar results regarding the participation of immigrants in leisure activities, physical activities should be encouraged not only for physical health but also for psychological aspects.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have reported linear positive associations between levels of DSM skills and self-efficacy and participation in specific self-management behaviour, such as diet control, monitoring of blood glucose [24], physical exercise [25,26], foot care [27], as well as overall self-management behaviours [23,[28][29][30][31]. This implies that participation in disease self-management behaviours is an end-product of an individual's management skills and confidence to perform the behaviour.…”
Section: Introductionmentioning
confidence: 99%